2014
DOI: 10.3139/217.2862
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Plasticating Injection Molding – Experimental Assessment

Abstract: Ac omputational model for the description of polymer flow during the plasticating phase of the injection molding process is proposed. The polymer behavior is determined during the dynamic and static phases of the process. The model takes into account the backwards movement of the screw, the presence of anon-return valve and the conduction of heat during the idle times. Results for the dynamic and static phases of the plasticization are presented. The model is also used to study the influence of some important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…For the static melting, the equations that result from the solution of the Neumann problem 57 were applied. Fernandes et al 58 presented a computational model for the description of polymer flow during the plasticating phase of the IM process. The polymer behavior is determined during the dynamic and static phases of the process.…”
Section: Plasticatingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the static melting, the equations that result from the solution of the Neumann problem 57 were applied. Fernandes et al 58 presented a computational model for the description of polymer flow during the plasticating phase of the IM process. The polymer behavior is determined during the dynamic and static phases of the process.…”
Section: Plasticatingmentioning
confidence: 99%
“…Different 2D and 3D examples were suggested to validate the approaches presented and to illustrate its capabilities. 10,[43][44][45][46] Summarizing, it is generally recognized that computer aided engineering (CAE) simulations for IM can be outlined back to the 49 No Yes Donovan 50 Yes Yes Lipshitz et al 51 No Yes Rauwendaal 52 No Yes Potente et al 53 Yes Yes Yung and Xu 54 No Yes Yung et al 55 No Yes Steller and Iwko 56 No Yes Fernandes et al 58 Yes Yes pioneering research done by Kamal and Kenig 8 on the developments of the theoretical principles and fluid mechanics models. To apply 1D flow representations to simulate polymer flow in typically complex mold cavities, a "branching flow" approach was proposed and implemented.…”
Section: Researchmentioning
confidence: 99%
“…It consists of a dynamic extrusion melting model for the rotation period, a transient heat conduction model with a phase transition for the screw rest period, and a model for the drifting of the beginning of melting during the injection cycle. Later, the basic research in this field was performed first by Potente et al [136,137], and then by Steller et al [138,139] as well as by Covas et al [140]. Recently, Wilczyński et al [141] performed experimental studies on the melting mechanism of polymers in injection molding machines.…”
Section: Melting Sectionmentioning
confidence: 99%
“…It has been observed that melting in the injection molding machine occurs to some extent, according to the Tadmor mechanism, with clearly visible starvation (Figure 8). The existing models of the injection molding process (plasticating unit) [136][137][138][139][140] differ from the extrusion models in that they involve the static and dynamic phases of melting (stationary and rotating screw) with an axial screw movement. However, it is assumed that the screw is fully filled with a material such as in the flood fed extrusion (Figure 2), which is inconsistent with Figure 8 where starvation is clearly seen in the starve fed extrusion (Figure 4).…”
Section: Melting Sectionmentioning
confidence: 99%
“…The studies for twin‐screw extrusion, both co‐rotating and counter‐rotating , have been carried out by White et al The studies in this area for starve fed single‐screw extrusion have been performed by Wilczyński et al . Extrusion experiences have been successfully adapted for modeling of injection molding process, for example, by Potente et al , Steller et al , and recently by Fernandes et al . These studies have been summarized by Altinkaynak et al and Wilczyński et al .…”
Section: Introductionmentioning
confidence: 99%